Will you teach me? A didactic experience involving Infant and Sacondary students - García-Lago Ibáñez, Virginia; García González, Juan Carlos; Vaquero Martín, Sandra (Pulso. Revista de educación, 2013)
This article gathers the didactic experiences that have been recently undertaken at Santa Maria College, an experience which was born with a triple motivation: To promote a sense of unity cohesion between the students in Childrens Education and the students in Secondary Education. Improve the digital competences of all the students. Learn History in a playful and more appealing way. To pursue this aim the students of the second cycle of Secondary Education created digital activities and designed teachable sessions for their counterparts in the 3rd level of Childrens education (5 years old). Taking into account that all aims were achieved and the programmed skills were developed, the evaluation of the project was very gratifying for all members involved.
Keywords: History Didactics; Digital Comptence; Emotional Competence